2022
DOI: 10.3389/fimmu.2022.1023164
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of anti-orthopoxvirus immunity in Moscow residents and potential risks of spreading Monkeypox virus

Abstract: WHO has declared the outbreak of monkeypox as a public health emergency of international concern. In less than three months, monkeypox was detected in more than 30 000 people and spread to more than 80 countries around the world. It is believed that the immunity formed to smallpox vaccine can protect from monkeypox infection with high efficiency. The widespread use of Vaccinia virus has not been carried out since the 1980s, which raises the question of the level of residual immunity among the population and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In epidemiological and epizootological terms, this property of the new virus is a potentially dangerous and naturally causes concern. Moreover, in recent years, natural populations of various representatives of the smallpox virus have become more active in the world [ 30 , 31 , 32 ]. We admit the possibility of expanding the ecological and virological competencies of ticks containing pathogens such as the Kiparis-144 virus.…”
Section: Discussionmentioning
confidence: 99%
“…In epidemiological and epizootological terms, this property of the new virus is a potentially dangerous and naturally causes concern. Moreover, in recent years, natural populations of various representatives of the smallpox virus have become more active in the world [ 30 , 31 , 32 ]. We admit the possibility of expanding the ecological and virological competencies of ticks containing pathogens such as the Kiparis-144 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 shows the characteristics of the included studies. One study was conducted across countries [34]; one study across Europe [35]; twenty studies in USA [26,33,[36][37][38][39][40][41][42][43][44][45][46][47][48][49]; four studies in Democratic Republic of the Congo (DRC) [50][51][52][53]; two studies in Israel [54,55], Netherlands [56,57], United Kingdom (UK) [58,59], and France [60,61]; one study in Congo [62], China [63], Italy [64], Germany [65], Russia [66], Australia [67], and Spain [68]. All studies except three [57,69,70] were peer-reviewed.…”
Section: Summary Of the Included Studiesmentioning
confidence: 99%
“…Of note, the production of antibodies differed across ages: NAbs titer of 1/20 or more in 33.3 to 53.2% of people older than 45 years. Among people 30-45 years old who probably have not been vaccinated, the proportion with virus NAbs ranged between 3.2 and 6.7% [66].…”
Section: Immunogenicitymentioning
confidence: 99%
See 1 more Smart Citation
“…A mouse model of VACV infection suggested that CD4+ T-cell-dependent anti-VACV antibody production plays an important role in clearing the virus following acute infection, while in the absence of antibodies, CD8+ T cells can contribute to protection against the disease [3]. It is believed that the smallpox vaccine confers lifelong protection against severe disease [10], and studies carried out after smallpox eradication tried to estimate the waning effect by measuring the levels of immunological markers at different time-points post-immunization [11][12][13][14][15][16][17][18][19][20][21]. Nowadays, after smallpox eradication and the discontinuation of the vaccination campaign, the human population is largely unvaccinated.…”
Section: Introductionmentioning
confidence: 99%